2016
DOI: 10.1002/smll.201600065
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Modes Induced by Anisotropic Gap Opening in Au@Cu2O Nanorods

Abstract: Integration of semiconductors with noble metals to form heteronanostructures can give rise to many interesting plasmonic and electronic properties. A number of such heteronanostructures have been demonstrated comprising noble metals and n-type semiconductors, such as TiO2 , ZnO, SnO2 , Fe3 O4 , and CuO. In contrast, reports on heteronanostructures made of noble metals and p-type semiconductors are scarce. Cu2 O is an unintentional p-type semiconductor with unique properties. Here, the uniform coating of Cu2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…In previous works, the silver nanowire is usually placed on the dielectric substrate. [36][37][38][39] In this case, it is observed that the effective refractive index (n eff ) of the SPP waveguide mode decreases with the increase of the radius of the silver nanowire (black line with rectangle symbols in Figure 2b), which is opposite to the case when the silver nanowire is placed on the silver substrate (black line with rectangle symbols in Figure 2a). As a result, the SPP waveguide mode supported by the silver nanowire (placed on the glass substrate) is cutoff (the green dashed line in Figure 2b) when the radius of the silver nanowire is greater than 44 nm (r > 44 nm).…”
Section: Spp Waveguide Mode With Long Propagation Length and Without mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, the silver nanowire is usually placed on the dielectric substrate. [36][37][38][39] In this case, it is observed that the effective refractive index (n eff ) of the SPP waveguide mode decreases with the increase of the radius of the silver nanowire (black line with rectangle symbols in Figure 2b), which is opposite to the case when the silver nanowire is placed on the silver substrate (black line with rectangle symbols in Figure 2a). As a result, the SPP waveguide mode supported by the silver nanowire (placed on the glass substrate) is cutoff (the green dashed line in Figure 2b) when the radius of the silver nanowire is greater than 44 nm (r > 44 nm).…”
Section: Spp Waveguide Mode With Long Propagation Length and Without mentioning
confidence: 99%
“…From the fabrication point of view, the nanoslit can be etched by helium-focused ion beam (Carl Zeiss Orion Plus helium ion microscope) in the single-crystalline silver nanowire. [49,50] In the previous work reported by Xu's group, [39] a slit with a width of 18 nm on the single-crystalline silver nanowire could be fabricated by using gallium FIB (FEI DB235). Moreover, Xu's work [39] reported that the effect of the ion beam had a minor influence on the silver nanowire waveguide properties.…”
Section: Guiding the Single-photon Emission In The Waveguide-slit Strmentioning
confidence: 99%
See 1 more Smart Citation
“…It has nano-scaled size in one or all three dimentions and can interact resonantly with emitters through the strong near field. Plasmonic cavities and waveguides have been proposed as buliding blocks for highly integrated photonic circuits [13]. However, due to absorption in metal, plasmonic cavities have high losses and low quality factors.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement is much larger than for SR in free space. Here we consider plasmonic SR, i.e., emitters generate plasmons, as in [13], not photons. Our approach can be easily generalized to many emitters and used for calculating the statistical properties of SR as in [6].…”
Section: Introductionmentioning
confidence: 99%